2014
DOI: 10.1186/1757-7241-22-17
|View full text |Cite
|
Sign up to set email alerts
|

Brief hospitalizations of elderly patients: a retrospective, observational study

Abstract: BackgroundCrowded departments are a common problem in Danish hospitals, especially in departments of internal medicine, where a large proportion of the patients are elderly. We therefore chose to investigate the number and character of hospitalizations of elderly patients with a duration of less than 24 hours, as such short admissions could indicate that the patients had not been severely ill and that it might have been possible in these cases to avoid hospitalization.MethodsMedical records were examined to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This is harmonized with a common understanding that the most problematic expression of an ageing population is the clinical condition of frailty [ 26 ]. For this population, it is of vital importance to apply a systematic approach in community care, in order to reduce the use of inappropriate procedures, iatrogenic diseases and nosocomial infections, which are associated with hospitalization [ 29 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is harmonized with a common understanding that the most problematic expression of an ageing population is the clinical condition of frailty [ 26 ]. For this population, it is of vital importance to apply a systematic approach in community care, in order to reduce the use of inappropriate procedures, iatrogenic diseases and nosocomial infections, which are associated with hospitalization [ 29 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is an ongoing discussion whether a proportion of the hospital admissions among older persons could have been prevented in primary treatment and care [ 7 , 27 , 28 ]. Studies from Scandinavia have found that older persons are hospitalized due to lack of an appropriate alternative in primary care [ 28 , 29 ], however a Norwegian study found no association between the volume of municipality general practitioners provided (in a universally accessible healthcare system) and unplanned hospitalizations of the entire elderly population (aged ≥65 years) [ 8 , 30 ]. The picture concerning the prevention of hospitalizations within this age group is thus not clear; heterogeneity in terms of health status and age-related conditions, as well as numerous contextual factors related to the health care system, represent a challenge for isolating factors concerning thematter.…”
Section: Introductionmentioning
confidence: 99%
“…10,11,12 Unnecessary hospitalizations of NH residents have been shown to increase health care costs and contribute to various negative patient outcomes. 2 One solution is to introduce new programs that can assist staff in rapidly identifying and managing acute changes in the condition of NH residents and respecting advance care directives.…”
Section: Impact Of Unnecessary Hospital Transfersmentioning
confidence: 99%
“…The underlying assumption is that the use of digital technologies can potentially redesign care pathways in a way that will improve monitoring and treatment of degenerative and chronic diseases, encourage better self-management of health problems, and alert professional support if devices signal a problem [2,3,[6][7][8][9], ultimately reducing the disruptive impact of acute unscheduled hospital admissions, for example, for older persons [10]. Previous research has identified that emergency hospital admissions often occur when an older person has reached a point of crisis because of a combination of circumstances, such as an exacerbation of a chronic condition, change in social setting, or a cascade of symptoms because of multimorbidity and frailty [11][12][13][14][15][16][17]. The use of eHealth could thus be applied as a tool to prevent a severe state of illness that requires hospitalization by discovering and addressing the patients' symptoms at an early stage.…”
Section: Introductionmentioning
confidence: 99%